Business Process Reengineering in the Training Service Business Process of CV. Maxindo Consulting to Improve Company Performance Efficiency - Ruben Emanuel Widagdo; Suartana, I Made (Universitas Negeri Surabaya, 2024)
In facing global competition, companies must ensure that employees can work effectively and efficiently, with both high-quality and high-quantity output. Employee training has become one of the crucial methods to meet these standards, considering the importance of competent human resources in supporting a company’s competitiveness. CV. Maxindo Consulting is a company that specializes in employee training services across various sectors. However, its current business processes, such as proposal requests and training evaluations, remain time-consuming, hindering work efficiency and potentially harming the company’s image. Therefore, Business Process Reengineering (BPR) is proposed as a solution. This BPR approach is expected to enhance service quality, operational efficiency, and the company’s positive image. The BPR method, as explained by Hammer and Champy (1994) and Davenport & Short (1990), represents a novel approach to business process improvements that can optimize company services and performance.